The Barriers of Adopting Digital Twin In Indonesian Industry: The Innovation Resistance Theory - Adven Firman Nauli Hutajulu; Khawarid Pasaribu; Afrizal Adi Panuluh (International Journal Labs, 2025)
This research examines barriers to digital twin adoption in Indonesian industries, by employing Innovation Resistance Theory (IRT). Indonesia's burgeoning energy demands necessitate decarbonization efforts, and digital twins offer a promising solution for improving energy efficiency to reduce emissions. However, their adoption lags. The study investigates functional (usage, value, risk) and psychological (image) barriers to adoption of digital twin. Hypotheses posit a positive relationship between each barrier and resistance to adoption of digital twin. The research also examines the moderating role of incentive policies in the relationship of each barrier and the resistance to adopt digital twin. By employing a quantitative approach with a cross-sectional survey of Indonesian industrial professionals, and PLS-SEM analysis, the study finds significant positive effects of usage, value, and risk barriers on resistance of adoption of digital twin. Image barriers show a weaker, non-significant influence. While incentive policies positively moderate the relationship between usage barriers and resistance, their impact on value and risk barriers is negative. These findings highlight the importance of addressing concerns about cost, technological superiority, and risk alongside the need for stronger, more targeted government support in addressing financial and risk-related aspects. Understanding the interplay of barriers and incentive policies is crucial for promoting digital twin uptake, fostering sustainable industrial growth in Indonesia. Further research could explore the specific contexts of various industrial sectors.